Multi-Omics Integration Analysis Identifies Lipid Disorder of a Non-Alcoholic Fatty Liver Disease (NAFLD) Mouse Model Improved by Zexie–Baizhu Decoction - Cao, Yuhan; Shi, Jingying; Song, Luyao; Xu, Junjiu; Lu, Henglei; Sun, Jianhua; Hou, Jinjun; Chen, Jing; Wu, Wanying; Gong, Likun (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is an increasingly epidemic metabolic disease with complex pathogenesis. Multi-target therapy may be an effective strategy for NAFLD treatment, and traditional Chinese medicine (TCM) characterized by multi-ingredients, multi-targets, has unique advantages in long-term clinical practice. Zexie-Baizhu (ZXBZ) decoction is a Chinese classical formula to treat body fluid disorders initially. Although many bioactive monomers from Zexie and Baizhu have been discovered to improve lipid disorders, there are limited researches on aqueous ZXBZ decoction, the original clinical formulation. In current study, we identified 94% chemical composition of ZXBZ decoction and firstly discovered its hepaprotective effect in Gubra-Amylin NASH (GAN)-diet induced NAFLD mouse model. Based on metabolomics and transcriptomics analyses, we speculated that lipid and glucose metabolisms might be regulated by ZXBZ decoction, which was further confirmed by the improved dyslipidemia and hepatic steatosis in ZXBZ groups. Consistently with cross-omics analysis, we discovered ZXBZ decoction could activate two energy sensors, Sirt1 and AMPK, subsequently change related genes involved in lipogenesis, lipid catabolism, and lipid transport. In conclusion, ZXBZ decoction regulated energy sensors, consequently impeded lipogenesis and promoted FAO to alleviate dyslipidemia and hepatic steatosis and protect liver, which suggested ZXBZ decoction might be a promising treatment for NAFLD.